Baseline and Early On-Treatment Prognostic Nutritional Index in Hormone Receptor–Positive, HER2-Negative Metastatic Breast Cancer Treated with CDK4/6 Inhibitors - Ezgi Çoban; Atilla Eren Kurt; Fırat Akagündüz; Ahmet Demirel; Mustafa Alperen Tunç; Burak Paçacı; Ali Kaan Güren; Erkam Kocaaslan; Pınar Erel; Yeşim Ağyol; Abdussamet Çelebi; Selver Işık; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: The prognostic nutritional index (PNI) has been associated with outcome in metastatic breast cancer, but studies in CDK4/6 inhibitor-treated patients have used cohort-derived thresholds and examined only the pretreatment value. We assessed the PNI as a continuous variable, compared it with inflammatory indices, and examined whether repeated measurement added information. Methods: We reviewed 192 consecutive patients with hormone receptor–positive, HER2-negative metastatic breast cancer treated with a CDK4/6 inhibitor and endocrine therapy at a single centre. We calculated the PNI, neutrophil-to-lymphocyte ratio (NLR), and systemic inflammation response index (SIRI) before treatment and recalculated them before cycles 2 and 3. The Cox models were adjusted for age, liver metastasis and line of therapy; no threshold was derived from these data. Results: The median follow-up was 44.9 months. Each one-point increase in the baseline PNI was independently associated with lower hazards of progression (HR 0.952, 95% CI 0.923–0.983) and death (HR 0.919, 95% CI 0.884–0.956), corresponding to HR 0.782 (95% CI 0.670–0.918) and HR 0.656 (95% CI 0.540–0.799) per five-point increase. For overall survival, in formal comparisons on identical patient sets, neither the NLR nor the SIRI added prognostic information to a model containing the PNI (likelihood ratio p = 0.383 and p = 0.335), whereas the PNI added information to models containing either ratio (p < 0.001 and p = 0.004). In exploratory landmark analyses, change in the PNI added little to the baseline value; apparent associations between increases in the NLR or SIRI by cycle 3 and overall survival did not persist after winsorisation of extreme change scores. Conclusions: Baseline PNI, analysed as a continuous variable and without a data-derived threshold, was independently associated with progression-free and overall survival in this cohort. For overall survival, neither baseline inflammatory ratio added detectable prognostic information beyond the index, and repeated measurement during treatment added little to the baseline value, although the confidence intervals do not exclude modest effects. Because all patients received a CDK4/6 inhibitor and no comparator arm was available, these findings support a prognostic rather than a predictive interpretation, and external validation is required before the index can inform clinical decisions.